2002
DOI: 10.1177/112067210201200612
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience with Perfluorohexyloctane (F6H8) as a Temporary Endotamponade in Vitreoretinal Surgery

Abstract: F6H8 seems to be a promising tamponade agent for special cases of RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 11 publications
0
32
0
4
Order By: Relevance
“…F6H8 was the first PFA that was used as a long-term heavy tamponade in several clinical trials (Table 1). [11][12][13][14][15][16] It was left intraocularly up to 14 weeks; on average, F6H8 was removed around 8 weeks postoperatively (Table 1). Marked differences in the complications and results of individual cases within one series 15,16 as well between different series have been reported.…”
Section: Partially Fluorinated Alkanes and Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…F6H8 was the first PFA that was used as a long-term heavy tamponade in several clinical trials (Table 1). [11][12][13][14][15][16] It was left intraocularly up to 14 weeks; on average, F6H8 was removed around 8 weeks postoperatively (Table 1). Marked differences in the complications and results of individual cases within one series 15,16 as well between different series have been reported.…”
Section: Partially Fluorinated Alkanes and Alkenesmentioning
confidence: 99%
“…9,10 The next substance in use as a long-term heavy tamponade, one which achieved certification in Europe for several clinical studies in the early 2000s was perfluorohexyloctane (F6H8). While some authors found encouraging results, 11,12 other groups reported a plethora of complications and discouraged the use of F6H8 as a vitreous substitute. [13][14][15][16] Around the same time, two new tamponades showed promising results in initial experimental settings, OL62HV and O62, only too soon to be associated with a high failure rate and massive complications.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the main concerns because the dispersion reduces the volume of the tamponade agent, thus reducing the contact with the surface of the retina. 26,37,38 Hydrofluorocarbon oligomers, produced by joining two to four FALK molecules, have been developed to increase oligomer viscosity and to minimize dispersion. The OL62HV oligomer has a viscosity of 1750 mPa.s.…”
Section: Eyementioning
confidence: 99%
“…Desta forma pôde ser avaliado o possível efeito de substâncias liberadas pelo F 6 H 8 que poderiam estar presentes no meio de cultura. O teste de citotoxici-dade indireta e obtenção dos extratos foi delineado de acordo com recomendações internacionais (21) .…”
Section: Teste De Citotoxicidade Indiretaunclassified
“…Estudos com o perfluorohexiloctano como substituto do vítreo em olhos de coelhos não mostrou alterações retinianas importantes na microscopia ótica e eletrônica (19) e a experiência clínica com o F 6 H 8 , embora limitada, mostra respostas distintas quanto ao dano retiniano e resposta inflamatória, conforme diferentes trabalhos (20)(21)(22) . Apesar desses achados iniciais, e devido ao fato do F 6 H 8 ser um produto novo, estudos referentes a citotoxicidade desse composto são necessá-rios para comprovar a sua segurança.…”
Section: Introductionunclassified